If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 2p + 8 Reorder the terms: 6 = 8 + 2p Solving 6 = 8 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 6 + -2p = 8 + 2p + -2p Combine like terms: 2p + -2p = 0 6 + -2p = 8 + 0 6 + -2p = 8 Add '-6' to each side of the equation. 6 + -6 + -2p = 8 + -6 Combine like terms: 6 + -6 = 0 0 + -2p = 8 + -6 -2p = 8 + -6 Combine like terms: 8 + -6 = 2 -2p = 2 Divide each side by '-2'. p = -1 Simplifying p = -1
| 15-12(-7x-6)= | | 30=-10+4m | | 12/3*9+20=x | | (t+6)(t-6)=(t+7)(t-8)+9 | | 12/3=x | | -3/8m+1+-13/8m=5 | | 2/5(4y+2x) | | 10-82/3 | | -185=-5-9b | | 10-8/3 | | 2=6+k/4 | | 2x^4-5x^3-16x+40=0 | | 2x-(7/6)+(x/6)=(4x+3/6) | | 2x-(7/6)+(x/6)=(4x+3)/(6) | | 3h=0.12 | | 9e+10= | | 100e+10= | | 5=1/2(4)+4 | | 14=3.5*h/2 | | 10e+10= | | 6(x-9)-4(x+5)=-1 | | 1/2n15 | | y=(-1/2x)2+6x+3 | | (Y+3)(y-12)=0 | | x^2-11x+30=(x-5)(x+6) | | 1/4x+1/8=3/4x-7/8 | | M=2/5(4y+2x) | | 2(3+x)+5=x | | x-5+3x-21+12-3x=4x5 | | x+4+4x+10(x-1)= | | (Y+3)(y-12)= | | x(x+4)=x^2+4 |